Assessment of methods for volumetric quantification of intracerebral hematomas in computerized tomography images (2018)
This work evaluates the performance of computational methods aimed at volume generation of five intracerebral hematomas (ICH), present in multi-layer computed tomography images, by means of three complementary steps. First. A ground truth volume or reference volume (RV) is considered. This RV is obtained, by a neurosurgeon, using the manual planimetric method (MPM). In a second step, the volumetry of the 5 ICH’s is obtained considering both the original version of the ABC/2 method and two of its variants, identified in this paper as ABC/3 method and 2ABC/3 method. The ABC methods allow for calculating hematoma volume under the geometric assumption that the ICH has an ellipsoidal shape. In a third step, a smart automatic technique (SAT) is implemented to generate the three-dimensional segmentation of each ICH. In the context of the present work, the expression SAT method is used to refer to the new methodology proposed to calculate the volume of the ICH. In order to evaluate the performance of the SAT, the Dice coefficient (Dc) is used to compare the dilated segmentations of the ICH with the ICH segmentations generated, manually, by a neurosurgeon. Finally, the percentage relative error is calculated as a measure to evaluate the methodologies considered. The results show that the SAT method exhibits the best performance, generating an average percentage error of less than 3%.